2013
DOI: 10.1016/j.bbmt.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Dose Intensification of Busulfan in the Preparative Regimen is Associated with Improved Survival: A Phase I/II Controlled, Randomized Study

Abstract: Dose intensity is important for disease control in patients undergoing allogeneic stem cell transplantation. We conducted a phase I/II controlled adoptive randomized study to determine the optimal dosing schedule of i.v. busulfan. Patients with advanced hematologic malignancies, ≤ 75 years with HLA-compatible donor were eligible. All patients received fludarabine at 30mg/m2/d for 4 days and busulfan was administered in different doses in oral or i.v. formulations. As determined by the phase I trial, i.v. busul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, outside of this patient population, weight-based BU dosing without TDM has been predominantly used in RIC [29][30][31][32]. In the interest of trying to determine whether BU dosing in the FLU/BU regimen had any effect on disease control, 1 group evaluated 6 different BU dose cohorts, ranging from 3.2 mg/ kg to 12.8 mg/kg, and found that the 11.2 mg/kg dose cohort, compared with all other predominantly lower dose cohorts, had improved overall survival (OS) and relapse-free survival [50]. However, another group compared 3.2 mg/kg daily to 6.4 mg/kg daily and found no difference in OS, diseasefree survival, GVHD, or NRM [29].…”
Section: Faq2: Is Bu Tdm Always Necessary?mentioning
confidence: 99%
“…However, outside of this patient population, weight-based BU dosing without TDM has been predominantly used in RIC [29][30][31][32]. In the interest of trying to determine whether BU dosing in the FLU/BU regimen had any effect on disease control, 1 group evaluated 6 different BU dose cohorts, ranging from 3.2 mg/ kg to 12.8 mg/kg, and found that the 11.2 mg/kg dose cohort, compared with all other predominantly lower dose cohorts, had improved overall survival (OS) and relapse-free survival [50]. However, another group compared 3.2 mg/kg daily to 6.4 mg/kg daily and found no difference in OS, diseasefree survival, GVHD, or NRM [29].…”
Section: Faq2: Is Bu Tdm Always Necessary?mentioning
confidence: 99%
“…This difference was probably due to the less frequent use of G-CSF in our institutions due to a preference for avoiding the use of G-CSF for myeloid malignancy. Actually, previous studies reported the faster engraftment of neutrophils with the use of G-CSF in patients with ivBU1 [7,9,17]. The incidence of VOD in the ivBU4 group was significantly higher than that in the ivBU1 group.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, dose finding studies of busulfan (16) and melphalan (17) have been conducted, and the reported optimal dose were 11.2 mg/kg and 135 mg/m 2 , respectively. Therefore, the antitumor effect of busulfan may be lower than that of melphalan in the RIC allo-HSCT setting.…”
Section: Discussionmentioning
confidence: 99%
“…Fludarabinebased regimens have been used as conditioning regimens for allo-HSCT in patients who must avoid cyclophosphamide toxicity or high-dose total body irradiation (TBI). Although fludarabine-based regimens with melphalan or busulfan have been widely used (2)(3)(4)(5)(6)(7)(8), and there have been several retrospective reports comparing the two regimens (9)(10)(11), there have been no randomized, controlled trials to compare these two regimens. We believed that an understanding of the current status is important to conduct prospective trials in the future.…”
Section: Introductionmentioning
confidence: 99%